Intimate partner violence against women in west Ethiopia: a qualitative study on attitudes, woman's response, and suggested measures as perceived by community members - Abeya Sileshi; Afework Mesganaw; Yalew Alemayeh (BMC, 2012)
Abstract Introduction Intimate partner violence against women is more prevalent in Ethiopia and among the highest in the world. This study was aimed to explore the attitudes of the community on intimate partner violence against women, the strategies women are using after the violence act, and suggested measures to stop or reduce the act in East Wollega Zone. Methods A total of 12 focus group discussions involving 55 men and 60 women were conducted from December, 2011 to January, 2012. Discussants were purposefully selected from urban and rural settings of the study area. The analyses followed the procedure for qualitative thematic analysis. Results Three themes (attitudes, coping strategies, and suggested measures) were emerged. Most discussants perceived, intimate partner violence is accepted in the community in circumstances of practicing extra marital sex and suspected infidelity. The majority of women are keeping silent and very few defend themselves from the violent husbands/partners. The suggested measures by the community to stop or reduce women's violence were targeting actions at the level of individual, family, community, and society. Conclusion In the study community, the attitude of people and traditional norms influence the acceptability for the act of intimate partner violence against women. Most victims are tolerating the incident while very few are defending themselves from the violent partners. The suggested measures for stopping or reducing women's violence focused on provision of education for raising awareness at all levels using a variety of approaches targeting different stakeholders. It is recommended that more efforts are needed to dispel myths, misconceptions and traditional norms and beliefs of the community. There is a need for amending and enforcing the existing laws as well as formulating the new laws concerning women violence including rape. Moreover, providing professional help at all levels is essential.